From Classical to Unwelded - An Examination of Four Knot Classes - Parchimowicz, Michael (My University, 2011)
This thesis is an introduction to virtual knots and the forbidden moves, and the closely related classes of welded and unwelded knots. Extensions of the Jones polynomial and the knot group to the various knot types are considered. We also examine the operation of connected sum for virtual and welded knots, and we review the proof that every virtual knot can be untied using the forbidden moves.
Keywords: Knot Theory; Virtual Knots; Welded Knots; Unwelded Knots; Geometry and Topology; Mathematics; Geometry and Topology